Integration of financial institutions supported with data asset development – Magyar Bankholding case study - Vajda, Gábor; Martzy, Antal; Lovász, Zoltán; Zéman, Zoltán (Public Finance Quarterly, 2023)
Magyar Bankholding was created as a result of the integration of three large banks, where digitisation and data centricity, including also the creation of efficient data asset management, were emphasised from the very beginning. Our study investigates, as a case study, whether a survey and preparation work based on the maturity assessment method can shorten the implementation time of a data asset, estimated at 1 to 1.5 years, to 7 months in a complex bank integration process. The results were backtested one year after the work was completed, so all the effects could be evaluated. It can be concluded that the application of the methodology described in the study has had a positive impact not only on time requirements, but also on business, digitalisation and technological objectives.